A non-spectroscopic optical biosensor for the detection of pathogenic Salmonella Typhimurium based on a stem-loop DNA probe and retro-reflective signaling - Kim, Dong Woo; Chun, Hyeong Jin; Kim, Jae Ho; Yoon, Hyunjin; Yoon, Hyun C. (Nano Convergence, 2019)
The detection of foodborne pathogenic microorganisms is an essential issue in molecular diagnostics. Fluorescence-based assays have been widely utilized in molecular diagnostics because of their ability to detect and measure low analyte concentrations. However, conventional fluorescence-based assays require sophisticated optics systems, such as a specific light source and light filter. To overcome these limitations, we developed an optical sensing system using a retroreflective Janus microparticle (RJP) as a signaling probe. Compared to fluorescent dyes, RJPs have the advantage of not requiring complicated optic systems because they can be observed using visible light without a filter. To confirm that RJPs can be used as a probe for molecular diagnostics, Salmonella was detected using a biotinylated stem-loop DNA probe to capture the target gene DNA and a streptavidin-conjugated RJP (SA-RJP) as the detection molecule. When the target gene DNA was present at the sensing surface where the stem-loop DNA probe was immobilized, the biotinylated stem-loop DNA probe was stretched, exposing biotin, which can react with SA-RJP. Since the amount of exposed biotin increased according to the concentration of the applied target gene DNA, the number of observed RJPs on the sensing surface increased with the concentration of the target gene DNA. Consequently, the concentration of Salmonella could be quantitated by counting the number of observed RJPs. Using this system, Salmonella at concentrations ranging from 0 to 100 nM could be analyzed, with high sensitivity and selectivity, with a limit of detection of 2.48 pM.
Keywords: Molecular diagnostic; Optical biosensor; Retroreflective Janus particles; Salmonella; Stem-loop DNA